2022
DOI: 10.1021/acsami.1c23268
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Boron Nitride Memristive Device for High-Density Memory and Neuromorphic Computing Applications

Abstract: Although two-dimensional (2D) nanomaterials are promising candidates for use in memory and synaptic devices owing to their unique physical, chemical, and electrical properties, the process compatibility, synthetic reliability, and cost-effectiveness of 2D materials must be enhanced. In this context, amorphous boron nitride (a-BN) has emerged as a potential material for future 2D nanoelectronics. Therefore, we explored the use of a-BN for multilevel resistive switching (MRS) and synaptic learning applications b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 70 publications
3
23
0
Order By: Relevance
“…In a recent study, Khot et al demonstrated high-density memory applications of the CBRAMs in a-BN-based devices ( Figure 9 a) [ 58 ]. The Ag/a-BN/Pt device presents multilevel switching achieved by controlling the compliance current during the SET process, as shown in Figure 9 b.…”
Section: Memory Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Khot et al demonstrated high-density memory applications of the CBRAMs in a-BN-based devices ( Figure 9 a) [ 58 ]. The Ag/a-BN/Pt device presents multilevel switching achieved by controlling the compliance current during the SET process, as shown in Figure 9 b.…”
Section: Memory Applicationsmentioning
confidence: 99%
“…Reprinted from Ref. [ 58 ]. ( e ) The data retention time of 10 years at 177 °C was demonstrated by an Al 2 O 3 -based CBRAM device with Te as the AE material.…”
Section: Figurementioning
confidence: 99%
“…Nickel-based materials, particularly nickel oxides, have been widely investigated as a resistive switching material for high-density memory applications. The resistive switching devices are considered as artificial synapses upon the application of low-power electrical stimuli . Reports have been published on boron nitride, cobalt phosphate, copper oxide, zinc oxide, tantalum oxide, and titanium dioxide nanotube-based devices for high-density memory and/or neuromorphic computing applications. The nickel-based sulfide materials have wide applications in dye-sensitized solar cells, supercapacitors, rechargeable batteries, electrochemical sensors, oxygen evolution reactions, and photocatalysis. However, the neuromorphic performance study of nickel sulfide-based materials is still unexplored. For this reason, we have considered nickel sulfide nanomaterials for neuromorphic computing applications by fabricating a metal–insulator–metal type of device.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the demand for next‐generation non‐volatile memories (NVMs) has increased in both the consumer and industrial domains. [ 1 ] It is necessary to develop new device to realize the simultaneous storage and compute in one device to overcome von Neumann bottleneck. [ 2–4 ] Among the various types of NVMs, memristors, as an emerging and promising memory storage device, have attracted widespread attention due to their low cost, high density, long‐term data retention, fast operating speed, high endurance, and simple structure.…”
Section: Introductionmentioning
confidence: 99%